Characterization of cortical alveoli content in several species of Antarctic notothenioids - MOTTA, CHIARA MARIA; TAMMARO, STEFANIA; SIMONIELLO, PALMA; PRISCO, MARINA; RICCHIARI, LOREDANA; ANDREUCCETTI, PIERO; FILOSA, SILVANA (Journal of Fish Biology, 2005)
Cytochemical analyses was used to study the organization and content of cortical alveoli in eight species of Antarctic teleosts belonging to three different families of notothenioids: nototheniids, bathydraconids and channichthyids. Results indicated differences existed among the various species in alveolar size and distribution and in their content. In nototheniids, in particular, typical nucleoids were formed that could be large and single or small and multiple, according to the species considered. As demonstrated by the affinity to periodic acid‐Schiff (PAS) and lectin staining, these nucleoids were rich in glycoconjugates, whose nature was extremely varied in the different species, but not in lipo‐ or acidic proteins as indicated by Sudan Black B and silver salts staining. Protein extracts, electrophoresed and stained with Sudan, PAS and two lectins demonstrated that the alveoli in the two species, Trematomus bernacchii and Trematomus newnesi, contained c. 80 kDa protein rich in N‐acetylglucosamine groups. By contrast, the typical hyosophorins, described as the major alveolar content in other fishes, were apparently present only in T. newnesi.